Remarkably ruby ebook - Libenson, Terri (Emmie & Friends, 2022)
From bestselling author Terri Libenson, this is a story about how there's more to everyone than meets the eye. Pride. Popularity . . . Poetry? Middle school. Ruby and Mia are total opposites: Ruby is a little awkward, not a "joiner," and loves to write poetry. While Mia is type A, popular(ish), and wants to be class prez. They used to be friends. But now they have nothing in common anymore. . . . Or do they? Don't miss the rest of the Emmie & Friends series: Invisible Emmie, Positively Izzy, Just Jaime, Becoming Brianna, Truly Tyler, and You-Niquely You: An Emmie & Friends Interactive Journal!